Equipment for Monitoring Synchronous Generators Condition through External Magnetic Field Waveforms - L. O. S. Grillo; C. A. C. Wengerkievicz; H. F. dos Santos; N. J. Batistela; P. Kuo-Peng; N. Sadowski; T. K. Matsuo; C. L. de Souza; L. M. de Freitas; R. J. Nascimento (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2022)
Abstract This paper presents an equipment for monitoring synchronous generators condition through characteristics of the time derivative of the external magnetic field. The developed monitoring methodology allows the identification of established or incipient faults, by detecting changes in the magnetic signature of the synchronous generator. In this methodology, the measurement of signals outside the machine gives this equipment a non-invasive characteristic, allowing its monitoring without interfering or disturbing its operation. The developed system includes the specification of magnetic field sensors, signal measurement and processing equipment, as well as software for analysis and monitoring. The validation of the methodology used in this system was carried out through the analysis of experimental data, presenting efficient results in the detection of electrical and mechanical faults in synchronous generators of an experimental test bench and a hydroelectric power plant. As a result, the commercial specification of this equipment was obtained and two units were implemented in a hydroelectric power plant to monitor 305 MVA synchronous generators.